Cold science : environmental knowledge in the North American Arctic during the Cold War - Bocking, Stephen 1959- Herausgeber; Heidt, Daniel 1985- Herausgeber (Routledge studies in the history of science, technology and medicine;, 2019)
Science during the Cold War has become a matter of lively interest within the historical research community, attracting the attention of scholars concerned with the history of science, the Cold War, and environmental history. The Arctic--recognized as a frontier of confrontation between the superpowers, and consequently central to the Cold War--has also attracted much attention. This edited collection speaks to this dual interest by providing innovative and authoritative analyses of the history of Arctic science during the Cold War